Unveiling heterogeneous gaze patterns in autistic children undergoing rTMS: insights from latent profile analysis - Liu, Hong; Xu, Chang; Xiao, Yingchen; Tian, Li; Li, Yin; Zhang, Xin; Gao, Lei (Frontiers in Psychiatry, 2026)
AimRepetitive Transcranial Magnetic Stimulation (rTMS) is a promising intervention for Autism Spectrum Disorder (ASD), but objective markers for rTMS tolerance remain lacking. This case-control study explored gaze behavior variability toward emotional faces in ASD children undergoing rTMS, focusing on identifying subgroups associated with rTMS intolerance.MethodEye-tracking data (Tobii technology, preferential-looking paradigm) were collected from 104 ASD children (48 intolerant, 56 tolerant) receiving DLPFC-targeted rTMS (left high-frequency, right low-frequency). Latent Profile Analysis (LPA) identified fixation subgroups across eight conditions. Demographic (sex, age), clinical (CARS scores) differences, and profile-tolerance associations were analyzed.ResultsLPA revealed three gaze profiles: moderate non-preferential fixation (80.76%), low diverse fixation (9.62%), and increased fixation with mild variability (9.62%). Sex and CARS scores differed across profiles (age did not). Intolerance rates were 38.1%, 60.0%, and 100%, with profiles predicting rTMS intolerance (OR = 0.210, 95% CI: 0.079–0.557).ConclusionASD children exhibit heterogeneous emotional face gaze patterns. Findings highlight the need for personalized rTMS interventions, especially for those with higher CARS scores and increased emotional face fixation—at elevated intolerance risk.